Highly anisotropic Fe3C microflakes constructed by solid-state phase transformation for efficient microwave absorption - Zhao, Rongzhi; Gao, Tong; Li, Yixing; Sun, Zhuo; Zhang, Zhengyu; Ji, Lianze; Hu, Chenglong; Liu, Xiaolian; Zhang, Zhenhua; Zhang, Xuefeng; Qin, Gaowu (Nature communications, 2024)
Soft magnetic materials with flake geometry can provide shape anisotropy for breaking the Snoek limit, which is promising for achieving high-frequency ferromagnetic resonances and microwave absorption properties. Here, two-dimensional (2D) Fe 3 C microflakes with crystal orientation are obtained by solid-state phase transformation assisted by electrochemical dealloying. The shape anisotropy can be further regulated by manipulating the thickness of 2D Fe 3 C microflakes under different isothermally quenching temperatures. Thus, the resonant frequency is adjusted effectively from 9.47 and 11.56 GHz under isothermal quenching from 700 °C to 550 °C. The imaginary part of the complex permeability can reach 0.9 at 11.56 GHz, and the minimum reflection loss ( RL min ) is −52.09 dB (15.85 GHz, 2.90 mm) with an effective absorption bandwidth (EAB ≤−10 dB ) of 2.55 GHz. This study provides insight into the preparation of high-frequency magnetic loss materials for obtaining high-performance microwave absorbers and achieves the preparation of functional materials from traditional structural materials. Fe 3 C microflakes with high magnetic anisotropy are prepared through solid-state phase transformation and electrochemical dealloying. The magnetic anisotropy can be tuned by adjusting the morphology, resulting in optimized ferromagnetic resonance behavior for microwave absorption